Culture and perceptions of power in teacher-student communication - Erpestad, Mikko (2011)
The objective of this study was to find out if national culture impacts the phenomenon of power as it is found in teacher-student communication at the University of Jyväskylä. The study is pertinent and relevant because of the increasingly rapid internationalization that is happening in the Finnish higher education system. Understanding aspects of intercultural teacher-student communication will be important for the future.